2008
DOI: 10.1161/atvbaha.107.161653
|View full text |Cite
|
Sign up to set email alerts
|

Mouse CD36 Has Opposite Effects on LDL and Oxidized LDL Metabolism In Vivo

Abstract: Objective-The cluster of differentiation-36 (CD36) is a multifunctional protein which is recognized for its in vitro ability to take up oxidized low-density lipoproteins (oxLDL) in macrophages and is therefore considered atherogenic. It also binds LDL. Our objective was to define the physiological role of CD36 in both native LDL and oxLDL metabolism in mice. Methods and Results-Clearance studies of labeled LDL and oxLDL were conducted in wild-type, CD36 knockout (KO), scavenger receptor class B, type I (SR-BI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
6
38
1
Order By: Relevance
“…This consistent change in HDL steadystate level is in agreement with a physiologic function of CD36 in HDL metabolism in vivo. Plasma triacylglycerol and fatty acids were not different between CD36 KO and WT animals in this study; this observation is in contrast to a previous report ( 15 ) but in agreement with another study ( 11 ). However, mouse strain-related genetic differences and specifi c experimental conditions (like diet) presumably explain the discrepancy.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This consistent change in HDL steadystate level is in agreement with a physiologic function of CD36 in HDL metabolism in vivo. Plasma triacylglycerol and fatty acids were not different between CD36 KO and WT animals in this study; this observation is in contrast to a previous report ( 15 ) but in agreement with another study ( 11 ). However, mouse strain-related genetic differences and specifi c experimental conditions (like diet) presumably explain the discrepancy.…”
Section: Discussionsupporting
confidence: 74%
“…This molecule is expressed in skeletal and heart muscle, liver, lungs, adipose tissue, spleen, small intestine, testis, capillary endothelium, microglia, and elicited peritoneal macrophages ( 10,11 ). The ligands of CD36 include native and oxidized lipoproteins, anionic phospholipids, thrombospondin, collagen, amyloid b , and plasmodium falciparum-infected erythrocytes ( 4,5,11,12 ). With respect to metabolism, CD36 facilitates the transfer of fatty acids into myocytes ( 10 ).…”
Section: Hdl Metabolism In Micementioning
confidence: 99%
See 2 more Smart Citations
“…38-40 Although Luangrath et al showed that CD36 partly mediates oxLDL clearance in vivo, when large amounts of oxLDL are applyed, the residual clearance mechanism(s) are still unknown. 39 In contrast, plasma LAB was decreased when Del-1 was overexpressed. This could occur even if oxLDL concentrations were the same, because LAB measures LOX-1-binding activity, which is blocked by Del-1.…”
Section: Discussionmentioning
confidence: 98%